Comparison of serum biomarkers of myocardial fibrosis with cardiac magnetic resonance in patients operated for tetralogy of Fallot. (1st July 2022) - DiLorenzo, Michael P.; DeCost, Grace; Mai, Anh Duc; Hughes, Nkecha; Goldmuntz, Elizabeth; Jones, Andrea; Fogel, Mark A.; Mercer-Rosa, Laura
Abstract: Background: Serum biomarkers of myocardial fibrosis are considered markers of adverse outcome in adults with heart disease. Associations between biomarkers and clinical parameters in tetralogy of Fallot (TOF) has been understudied. We compared serum biomarker profiles with clinical and cardiac magnetic resonance (CMR) parameters of ventricular remodeling in patients with repaired TOF. Methods: Serum biomarkers [metalloproteinases MMP1 and MMP9, galectin-3, micro-RNA21 (miR21)), ST2, procollagen type I carboxy-terminal propeptide (PICP), and NTproBNP] were measured in TOF patients undergoing CMR. Associations between biomarkers and clinical and CMR variables were assessed using correlation coefficients, and linear and logistic regression. Results: Sixty patients were investigated, of which 47% were male. Age at CMR and TOF repair was 15 years [interquartile range (IQR) 9, 22] and 3.2 months (IQR 0.8, 6.2), respectively. Twelve (20%) had prior pulmonary valve replacement (PVR). MMP1 values were higher among those with prior PVR (16.7 (IQR 7.9, 25.5) vs 14.4 (IQR 9.9, 24.9), p = 0.02). When stratifying MMP1 into low and high groups, higher MMP1 was associated with higher indexed right (RV) and left ventricular (LV) mass and RV mass:volume ratios after adjusting for PVR. No other associations between biomarkers and CMR parameters were identified. Conclusions: Only MMP1 was associated with markers of RV remodeling after TOF repair. As an enzyme involved in extracellular matrix degradation, MMP1 could be associated with fibrotic processes underlying RV remodeling, including dilation and hypertrophy. The additional biomarkers may not be specific towards cardiac remodeling. These findings merit further correlations with myocardial fibrosis measurements by CMR. Highlights: Tetralogy of Fallot is associated with right ventricular (RV) remodeling. Metalloproteinase 1 (MMP1) is associated with higher indexed RV and LV mass by CMR. Other circulating biomarkers are not associated with ventricular remodeling by CMR.